Evaluation of the role of L-arginine on spermatological parameters, seminal plasma nitric oxide levels and arginase enzyme activities in rams - Kaya, Seyma Ozer; Kandemir, Fatih Mehmet; Gur, Seyfettin; Erisir, Mine; Benzer, Fulya; Kaya, Emre; Sonmez, Mustafa (Wiley, 2020)
The purpose of this study is to investigate the effects of L-arginine on spermatological parameters, seminal plasma nitric oxide levels and arginase enzyme activities. Fertile rams that are 2-3 years old and weighing 50-60 kg were used as material. The semen was collected by artificial vagina at 1st, 4th, 24th, 48th, 72nd, 96th and 120th hours for the control group before L-arginine administration. For treatment groups, L-arginine was administered intraperitoneally at a dose of 5 mg kg(-1) bw(-1) and semen was collected at the time point described for the control group. Spermatological characteristics of semen samples (semen volume, pH, sperm motility, concentration and abnormal sperm rate), seminal plasma nitric oxide levels and arginase enzyme activities were determined. Increased seminal plasma nitric oxide level (p < .01), seminal plasma arginase activity (p < .01), semen volume (p < .05), semen mass activity (p < .05), sperm motility (p < .05) and concentration (p < .01) and decreased abnormal sperm rate (p p < .01) were observed by L-arginine administration. In conclusion, it may be concluded that L-arginine application in rams during the breeding season may have positive effects on rams' reproductive performance.
Keywords: arginase activity; L-arginine; nitric oxide; ram; semen